Can the Library and the Data Archive Meet in Active Support of Research in the Social Sciences? The Case of ILSES - Repke de Vries (IASSIST Quarterly, 1999)
Can the Library and the Data Archive Meet in Active Support of Research in the Social Sciences? The Case of ILSES